Effect of Online Game’s Intensity on Verbal Aggression Behavior in students of SMP Negeri 10 Makassar - Muh. Nur Hidayat Nurdin; Faradillah Firdaus; Annisa Amalia Fajrianti; Nurul Fadilah; Muhrajan Piara (PT ARRUS Intelektual Indonesia, 2024)
Mobile Legends: Bang Bang is designed as a self-entertaining game that can stimulate adrenaline. One of the impacts of playing Mobile Legends: Bang Bang is verbal behavior that tends to be negative and aggressive which is caused by the high intensity of playing online games and even makes players unconsciously apply it in their daily lives. The large amount of free time that players use to play causes addiction and changes in the individual's character to become more aggressive. This research uses quantitative methods with accidental sampling techniques in sampling. The respondents in this research were students from SMP Negeri 10 Makassar who played the online game Mobile Legends: Bang Bang with an age range of 12-15 years with a sample of 117 students. The instruments used were the Online Game Playing Intensity scale and the Verbal Aggression scale. The data analysis used is simple regression analysis with the help of SPSS 24.0 software. The results of data analysis obtained a coefficient of determination (R Square) of 0.184 with a significance level of p = 0.000 (p < 0.05), so it can be concluded that the intensity of playing online games has a positive and significant influence on the verbal aggression of students at SMP Negeri 10 Makassar.